Characterization of the COVID-19 Vaccine Uptake in Patients With Chronic Diseases in a Large University-based Family Medicine Clinical Practice - Niharika Khanna; Elena Klyushnenkova; Min Zhan; Dae Hyoun Jeong; Colleen Kernan; David Stewart (SAGE Publishing, 2023)
Purpose: To characterize COVID-19 vaccine uptake in patients with chronic conditions at the large university-based Family Medicine practice serving a population with low COVID-19 vaccine acceptance. Methods: A rolling panel of patients attributed to the practice was submitted monthly to the Chesapeake Regional Health Information Exchange (CRISP) to monitor patients' vaccination status. Chronic conditions were identified using the CMS Chronic Disease Warehouse. An outreach strategy deploying Care Managers was developed and implemented. Associations between vaccination status and patients' characteristics were examined using a multivariable Cox's proportional hazard regression modeling. Results: Among 8469 empaneled adult (18+) patients, 6404 (75.6%) received at least 1 dose of COVID-19 vaccine in December 2020 to March 2022. Patients were relatively young (83.4% <65 years old), predominantly female (72.3%), and non-Hispanic Black (83.0%). Among chronic conditions, hypertension had the highest prevalence (35.7%), followed by diabetes (17.0%). Associations between vaccine status and the presence of chronic conditions varied by age and race. Older patients (45+ years old) with diabetes and/or hypertension showed a statistically significant delay in receiving COVID-19 vaccine, while young Black adults (18-44 years old) with diabetes complicated by hypertension were more likely to be vaccinated compared to patients of the same age and race with no chronic conditions (Hazard ratio 1.45; 95% CI 1.19,1.77; P  = .0003). Conclusions: The practice-specific COVID-19 vaccine CRISP dashboard helped to identify and address delays in receiving COVID-19 vaccine in the most vulnerable, underserved populations. Reasons for age and race-specific delays in patients with diabetes and hypertension should be explored further.